The impact of artificial selection for Wolbachia-mediated dengue virus blocking on phage WO. - Heverton L C Dutra; Suzanne A Ford; Scott L Allen; Sarah R Bordenstein; Stephen F Chenoweth; Seth R Bordenstein; Elizabeth A McGraw (Public Library of Science (PLoS), 2021)
Wolbachia is currently at the forefront of global efforts to control arbovirus transmission from the vector Aedes aegypti. The use of Wolbachia relies on two phenotypes-cytoplasmic incompatibility (CI), conferred by cifA and cifB genes in prophage WO, and Wolbachia-mediated pathogen blocking (WMPB). These traits allow for local, self-sustaining reductions in transmission of dengue (DENV) following release of Wolbachia-infected A. aegypti. Here, aided by previous artificial selection experiment that generated Low and High pathogen blocking lines, we examined the potential link between WMPB and phage WO. We found no evidence that Wolbachia or phage WO relative densities predict DENV blocking strength across selected lines. However, selection resulted in reduced phage WO relative density for the Low WMPB line. The Low blocking line was previously shown to have reduced fitness as a result of selection. Through subsequent genomic analyses, we demonstrate that SNP variation underpinning selection for low blocking led to elevated frequency of potential deleterious SNPs on chromosome 1. The key region on chromosome 1 contains genes relating to cell cycle regulation, oxidative stress, transcriptional pausing, among others, that may have cascading effects on Wolbachia intracellular environment. We hypothesize that reduction in phage WO may be driven by changes in the loci directly under selection for blocking, or by the accumulation of predicted deleterious alleles in linkage disequilibrium with blocking loci resulting from hitchhiking. For the Low line with fewer phage WO, we also detected reduced expression of cifA and cifB CI genes, with patterns of expression varying between somatic and reproductive tissues. In conclusion, we propose that artificial selection for WMPB trait had corresponding impacts on phage WO densities, and also the transcription of CI-causing genes. Future studies may include a more detailed analysis of the regions the A. aegypti chromosome 1's ability to affect WMPB and other Wolbachia-associated intrinsic factors such as phage WO.